94O Safety and antitumor activity of sitravatinib in combination with tislelizumab in patients with advanced solid tumors: Ovarian cancer cohort data. (15th December 2019) - Gao, B; Goh, J; Markman, B; Voskoboynik, M; Gan, H K; Coward, J; Palmieri, D; So, J; Meniawy, T; Chen, C; Xiang, X; Qiu, J; et al.
Abstract: Background: Sitravatinib is an investigational, orally bioavailable, receptor tyrosine-kinase inhibitor with immune modulatory and potential antitumor activity. Tislelizumab is an investigational, humanized IgG4 monoclonal antibody with high affinity and binding specificity for programmed cell death receptor-1 (PD-1). We assessed the safety and antitumor activity of sitravatinib plus tislelizumab in patients with advanced solid tumors. Methods: This is an open-label, multicenter, non-randomized, phase Ib study (NCT03666143). This cohort evaluated anti-PD-(L)1 antibody-naive patients with recurrent, platinum-resistant, epithelial ovarian cancer who were treated with 120 mg of sitravatinib once daily in combination with 200 mg tislelizumab every 3 weeks until disease progression, unacceptable toxicity, death, withdrawal of consent, or study termination. The primary objective was to assess the safety and tolerability of this combination therapy. Overall response rate, duration of response (DOR), disease control rate, and progression-free survival (PFS) were assessed as secondary endpoints. Results: As of 17 July 2019, 20 patients (median age, 66.0 years) were enrolled; median number of prior regimens was 5 (range, 2–12). All 20 patients received study drugs and were included in the safety analysis. Common (frequency ≥10%) grade ≥3 treatment-emergent adverse events (TEAEs) assessed as related to sitravatinib by investigators were hypertension (25%) and fatigue (10%). Six patients had AEs that led to sitravatinib discontinuation. The common (frequency ≥10%) grade ≥3 TEAE assessed as related to tislelizumab by investigators was increased transaminases (10%). Three patients had AEs that led to tislelizumab discontinuation. Of 17 efficacy-evaluable patients, 4 achieved confirmed partial response, 11 had stable disease, and 2 had progressive disease per RECIST version 1.1. Median PFS was 18.0 weeks; median DOR was not reached (NR) (both ranges, 12.29 weeks–NR). Conclusion: Combination treatment with sitravatinib and tislelizumab was manageable and showed promising antitumor activity in patients with ovarian cancer. Clinical trial identification: NCT03666143. Editorial acknowledgement: Writing assistance was provided by Ira Mills, PhD, of Ashfield Healthcare Communications. Legal entity responsible for the study: BeiGene. Funding: BeiGene. Disclosure: B. Gao: Advisory / Consultancy: Merck Sharp & Dohme. J. Goh: Advisory / Consultancy: Bristol-Myers Squibb, AstraZeneca, and Ipsen; Honoraria (self), Payment for speaking engagements: Merck Sharp & Dohme. B. Markman: Advisory / Consultancy: Novartis. M. Voskoboynik: Honoraria (self): AstraZeneca and MSD Oncology; Travel / Accommodation / Expenses: Bristol-Myers Squibb. H.K. Gan: Advisory / Consultancy: AbbVie, Bristol-Myers Squibb, and Merck Sharp & Dohme; Speaker Bureau / Expert testimony: Eisai and Merck Serono; Research grant / Funding (self): AbbVie. J. Coward: Advisory / Consultancy: Takeda and Merck Sharp & Dohme; Research grant / Funding (self): AstraZeneca. C. Chen: Shareholder / Stockholder / Stock options, Full / Part-time employment: BeiGene. X. Xiang: Shareholder / Stockholder / Stock options, Full / Part-time employment: BeiGene. J. Qiu: Shareholder / Stockholder / Stock options, Full / Part-time employment: BeiGene. Y. Xu: Shareholder / Stockholder / Stock options, Full / Part-time employment: BeiGene. L. Yang: Shareholder / Stockholder / Stock options, Full / Part-time employment: BeiGene. M. Millward: Advisory / Consultancy: Bristol-Myers Squibb, Merck Sharp & Dohme, Roche, and AstraZeneca. All other authors have declared no conflicts of interest.